AN EXPLORATION OF UNDERGRADUATE STUDENTS’ PERCEPTIONS OF AI-ASSISTED ENGLISH LEARNING TOOLS - Nurlaila Molla; Fajar Prihatini (English Review: Journal of English Education, 2025)
The growing incorporation of Artificial Intelligence (AI) in education has led to the widespread use of AI-assisted language learning applications. These tools introduce new approaches to improving English proficiency through features such as adaptive feedback and interactive practice. Gaining insights into students’ perceptions is essential for optimizing the role of such technologies in educational settings. This research investigated undergraduate students’ views on AI-assisted English learning, emphasizing their experiences, perceived advantages for language development, and the obstacles they faced. A qualitative design was applied, using semi-structured interviews with 20 English Language Education undergraduates at Universitas Pancasakti Tegal. All participants had engaged with AI tools—including Grammarly, QuillBot, and ELSA Speak—for at least three months. Data were examined through thematic analysis. The results showed that these tools enhanced learners’ vocabulary, grammatical accuracy, and pronunciation. Major benefits included individualized learning paths, responsive feedback, and a non-threatening practice environment that fostered autonomy and engagement. Nevertheless, several challenges emerged, such as the risk of dependency, occasional inaccuracies in AI-generated suggestions (particularly with cultural or idiomatic expressions), and concerns about reduced independent language production. The study also revealed a strong link between students’ digital literacy and their capacity to fully utilize AI tools. In conclusion, AI-assisted platforms serve as effective supplementary resources for English learning, offering meaningful support in personalization and skill building, though they cannot replace human instruction. Their success depends on thoughtful integration and user readiness. To optimize outcomes, it is recommended that educators embed AI literacy into curricula, while developers improve the cultural sensitivity and reliability of outputs. Ultimately, a balanced model that blends AI tools with human guidance is most beneficial for holistic language learning.